Mobius Bionic / Muhammad Idham Mahd Mayedi - Mahd Mayedi, Muhammad Idham (2022)
This is an effort to understand how the ideas should be put into practise. As an Uitm Arau student it is part of a case study project for all. Therefore, I have the ability to study an enterprise to produce an innovative idea for creativity. I refer bionic arm industrial that Bionic Mobius Company as my research company. Information is gathered through the internet source as well. Objective of the project is to work on the background, organizational structure and product that are provides. Also, I study about how bionic arm help the peoples with disabilities to have a normal life . Next, I research about the company financial achievements regarding how they manage their financial as well as achievements gain from the financial management. Goals indicate what a business unit wants to achieve and strategy is an action plan for getting the goals. In this study, I analysed the strength, weaknesses, opportunities and threats of this company in real business world by using SWOT analysis.